Significant incidents during X-ray exposures in humans – assessment and findings of the Federal Office for Radiation Protection - Winter, Katharina Stella; Schweden, Monika; Brix, Gunnar; Mille, Erik (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
In Germany, significant incidents must be reported to the competent authority since 12/31/2018 (section 108 Radiation Protection Ordinance (StrlSchV)). After assessment and evaluation of the reports, the competent authority submits the relevant information via a web-based reporting system (BeVoMed) to the Federal Office for Radiation Protection (BfS), which publishes the results derived therefrom. The present paper evaluates significant incidents related to X-ray exposures on humans.All reports on incidents in X-ray diagnostics and interventional radiology between 01/2019 and 10/2023, which were completed with detailed information until the reporting day (31/10/2023), were included. The following aspects were statistically evaluated: classification as an incident (section 1 subsection (22) StrlSchV), significance (section 108 StrSchV), classification to Annex 14 StrlSchV, assignment to the forms of care in the German healthcare system, and development of the reporting frequency over time. Furthermore, the content of the reports was systematically evaluated with regard to conspicuous clusters and typical problems.Until the reporting day, 383 reports (355 completed) were received. 252 reports (228 in X-ray diagnostics, 24 in interventional radiology) referred to significant incidents and were included in the detailed evaluation. Reporting frequency increased in X-ray diagnostics, whereas there was no trend in interventional radiology. Most of the significant incidents concerned examinations on an individual person (category I, criterion 2a or category II, criteria 2a and 3a) in the in-patient sector – especially in maximum care hospitals. Frequent errors concerned the inappropriate choice of parameters/protocols or were related to the administration of a contrast agent. Despite the overall positive trend, the establishment of awareness and error culture remains challenging.In Deutschland besteht seit dem 31.12.2018 eine Meldepflicht für bedeutsame Vorkommnisse gegenüber der jeweils zuständigen Behörde (§ 108 Strahlenschutzverordnung (StrlSchV)). Diese übermitteln nach Prüfung und Bewertung der Meldung relevante Informationen über ein webbasiertes Meldesystem (BeVoMed) an das Bundesamt für Strahlenschutz (BfS). Das BfS veröffentlicht daraus gewonnene Erkenntnisse. Die vorliegende Arbeit untersucht bedeutsame Vorkommnisse bei Röntgenanwendungen am Menschen.Die vorliegende Auswertung berücksichtigt alle Meldungen zu Röntgenuntersuchungen und -interventionen zwischen 01/2019 und 10/2023, für welche bis zum Stichtag (31.10.2023) eine Abschlussmeldung mit Detailinformationen vorlag. Statistisch ausgewertet wurden: Einordnung als Vorkommnis (§ 1 Abs 22 StrlSchV), Bedeutsamkeit (§ 108 StrlSchV), Klassifikation nach Anlage 14 StrlSchV, Zuordnung zu den Versorgungsformen im deutschen Gesundheitssystem sowie die zeitliche Entwicklung der Meldefrequenz über den Auswertewertezeitraum. Zudem wurden die Meldungsinhalte systematisch bezüglich auffälliger Häufungen und typischer Probleme ausgewertet.Zum Stichtag lagen dem BfS 383 Meldungen (355 abgeschlossene) vor. 252 Meldungen (228 zur Röntgendiagnostik, 24 zur Röntgenintervention) betrafen bedeutsame Vorkommnisse und gingen in die detaillierte Auswertung ein. Für die Röntgendiagnostik zeigt sich ein Anstieg der Meldefrequenz über den Auswertezeitraum, bezüglich der Intervention war kein Trend erkennbar. Die meisten bedeutsamen Vorkommnisse betrafen Anwendungen bei Einzelpersonen (Kategorie I, Kriterium 2a; Kategorie II, Kriterium 2a/3a) im stationären Bereich – insbesondere in Krankenhäusern der Maximalversorgung. Ein Problemfeld bildete die fehlerhafte Parameter-/Protokollanwahl, daneben kam es zu Problemen und Fehlern in Zusammenhang mit der Kontrastmittelgabe. Trotz der insgesamt positiven Entwicklung stellt die weitere Etablierung eines angemessenen Problembewusstseins und einer entsprechenden Fehlerkultur eine Herausforderung dar.
Keywords: significant incidents; incident reporting system; radiation safety; diagnostic radiology; interventional procedures